TOLAK UKUR FUNGSI HATI BERDASARKAN DERAJAT FIBROSIS PENYAKIT HATI KRONIS (Liver Function Parameters based on Degree of Liver Fibrosis in Chronic Liver Disease) - Rahmafitria Rahmafitria; Mutmainnah Mutmainnah; Ibrahim Abdul Samad (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Evaluating the degree of liver fibrosis degree is invasive as well as uncomfortable, therefore, non invasive examinations such as liverfunction tests and elastography (Fibro Scan) as a predictor‘s device of liver fibrosis degree are necessary. The aim of this study was toknow the differences of liver function parameters based on the fibrosis degree in patients with chronic liver disease. This study was a crosssectional design using data from chronic liver disease patients treated at the Dr. Wahidin Sudirohusodo Hospital. The elasticity of the liverwas measured using a fibro scan device during June 2010–July 2011. The analysis was carried out by ANOVA test on various parametersof liver function particularly on the fibrosis degree in chronic liver disease. In this study PT, albumin, total bilirubin and platelet countshowed a significant difference of 0.019, 0.009, 0.017 and 0.000 respectively. The mean values of PT and total bilirubin were significantlyhigher in the high degree of fibrosis compared to those with medium and low degree of fibrosis in the chronic liver disease patients. Basedon this study, the mean albumin levels and platelet count were significantly lower in the high degree of fibrosis compared with the mediumand low degree of fibrosis, however, no significant differences in AST, ALT, APTT and GGT were found.